Seismic Capacity Assessment of Confined Brick Masonry Building: An Experimental Approach - Asfandyar Ahmed; Imad Ahmad; Khan Shahzada; Muhammad Tayyab Naqash; Bashir Alam; Muhammad Fahad; Sajjad Wali Khan (Shock and Vibration)
Brick masonry is widely used for building construction throughout the world. However, unreinforced brick masonry buildings performed poorly in the 2005 Kashmir earthquake, in Pakistan, resulting in a decline in the use of brick masonry. In order to investigate and quantify the performance of brick masonry against the seismic forces by confining it through typical stiffer, line elements (column and beams), a full-scaled room model of an area 3048 × 3658 mm (10 × 12 ft) and height of 3353 mm (11 ft) was constructed using confined brick masonry. The model was tested under quasistatic loading system. Crack pattern was noted at the end of each loading cycle. The response of the model was interpreted through a hysteresis curve, which was then idealized by a bilinear curve. A comparison of the results has been made with four different studies done on the similar model made of unreinforced brick masonry before and after retrofitting and unreinforced concrete block masonry before and after retrofitting previously tested at the same testing facility.